Conservation pest control with new technologies: public perceptions. Issue 1 (1st January 2022) - MacDonald, Edith Anne; Neff, Mary Beth; Edwards, Eric; Medvecky, Fabien; Balanovic, Jovana
ABSTRACT: New genetic tools can potentially mitigate the decline of biodiversity. Democratisation of science mandates public opinion be considered while new technologies are in development. We conducted eleven focus groups in New Zealand to explore three questions about novel technologies (gene drive and two others for comparison of pest control tools): (1) what are the risks/benefits? (2) how do they compare to current methods? and (3) who should be represented on a panel that evaluates the tools and what factors should they consider? Findings from the content analysis of the risks/benefits revealed three main considerations that were of social concern – Environmental, Practical, and Ethical. Most participants were self-aware of their insufficient knowledge to compare the different technologies. Unanimously, respondents wanted the available information provided throughout the tool development process and saw multi-sector panel oversight as essential. Scientists and policy makers should match the public's willingness to engage collaboratively.